Studi Meta-Analisis: Aplikasi Teori Perubahan Perilaku Terencana (TPB) dalam Pemanfaatan Skrining Kanker Payudara - Elvira Purnamasari; Dini Hapsari (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
In 2022, there were 2.3 million women diagnosed with breast cancer and 670,000 deaths recorded worldwide. Women aged 30-49 years have a higher potential to have pre-cancerous lesions so that screening is one of the most effective and cheapest methods to detect cancer cells early. Breast self-examination (BSE) is an effective and easy-to-teach screening if other types of screening are difficult to access. Theory of Planned Behavior (TPB) as a theory of behavioral change that focuses on internal cognitive behavioral factors. This study is a systematic review and meta-analysis study using secondary data that has been published in the last 10 years from 3 databases, namely: Pubmed, Google Scholar and Science Direct. The keywords used were “Breast Cancer Examination” OR “Breast Cancer Screening” AND “Theory of Planned Behavior” OR “attitude” OR “perceived behavioral control” OR “self-efficacy”. The articles used were English articles with a cross-sectional design. Articles were collected using the PRISMA flow diagram and analyzed using the Review Manager 5.4 application. A total of 18 cross-sectional articles from Ethiopia, Thailand, Nepal, Rwanda, East Africa and Nigeria were analyzed using meta-analysis. The total number of research subjects was 58,799. The results of the meta-analysis showed that positive attitudes (aOR = 1.74; 95% CI = 1.35 to 2.23; p <0.00) and strong perceived behavioral control (aOR = 1.31; 95% CI = 1.17 to 1.48; p <0.001) increased the utilization of breast cancer screening. Positive attitudes and strong perceived behavioral control can increase the utilization of breast cancer screening.